General strategy for stereoselective synthesis of 1-substituted Exo,Endo-2,6-diaryl-3,7-dioxabicyclo[3.3.0]octanes: Total synthesis of (±)-gmelinol - Manat Pohmakotr (2018)
A general strategy for stereoselective synthesis of 1-substituted exo,endo-2,6-diaryl-3,7-dioxabicyclo[3.3.0]octanes including (±)-gmelinol from (2,3-trans)-(4,5-cis)-α-aroylparaconic esters, which are readily obtained from the reaction of vicinal dianions derived from α- aroylsuccinic esters with aromatic aldehydes, is described. The synthetic sequence involves α-methylation or α-hydroxylation, reduction, bislactonization, and reduction followed by furofuran formation. © 2006 American Chemical Society.